Main strategies of specialists’ team work on psychosocial support for women with alopecia - Zhyvylko, V. V. (Journal of Education, Health and Sport, 2017)
In compliance with the principles of bioethics and deontology, during 2013-2017, acomprehensive examination of women with a diagnosis of «total alopecia» was conducted on the basis of the Center for Reconstructive and Restorative Medicine of the Clinic of theOdessaNationalMedicalUniversity. 233 women aged 22 - 45 years old were examined. 76 persons had passed outpatient comprehensive course of author therapy, and 62 persons received treatment in accordance with the «Clinical protocol» but did not receive comprehensive psychosocial assistance. The patients under examination had violations in psycho-emotional, personal level, level of social functioning. A range of measures of psychosocial support, aimed at providing qualified transdisciplinary help to the patients and their families have been worked out. Their effectiveness is proved on the basis of evidence-based medicine. Within the framework of the research the peculiarities of the psychoemotional sphere of women with total alopecia are determined. Scientifically substantiated, developed and implemented in practice psychosocial support of women with total alopecia, which consisted of psycho-corrective measures using modern mobile e-health technologies. Approbation of measures of psychosocial support showed their effectiveness in 70,89% of cases (р≤0,05). Due to the allocation and systematization of predictors, provocative and supporting factors of diseases, the system of modular medical and social prevention of total alopecia in women was developed, which includes three modules: universal, indicative and selective prevention.